Unwanted Behavior Interventions in the Group of Four Students with ASD. The Individualized Reinforcement System - T.V. Sheptunova (Moscow State University of Psychology and Education, 2022)
Specific developmental deficits in children with autism spectrum disorders (ASD), such as difficulties in social in- teraction, disorders in the development of communication and speech development, limitations and stereotyping of interests, often lead to the development of the undesirable behavior in society, often dangerous for the child himself or the people around him. In its turn it leads to difficulties of social adaptation, prevents children from staying in the peer team, makes it difficult or impossible for children to learn. The article describes the case of the intervention for the simulations work with various manifestations of undesirable behavior in a group of students with ASD and intellectual development disorders in school conditions using a system of incentives, methods of individual selection of effective motivational stimuli, features of using a token system to form self-control. The data of the experimental study show the effectiveness of the system of incentives in the conditions of group work. The description of the stages of the introduction of this system allows teachers to use a similar system to correct student behavior and increase the efficiency of the educational process.